A comparison of the effectiveness of escape room and team-based learning in adult nursing class: A quasi-experimental study - Sukwon Hahn; Young Mi Ryu (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: To evaluate the effectiveness of an escape room as an educational intervention in an adult nursing class, as compared to team-based learning.Methods: A non-equivalent control group pretest-posttest design with a time lag was used to examine changes in knowledge, problem-solving proactivity, teamwork, learning motivation, and learning satisfaction at a university located in a C city. Seventy-three nursing students participated, with 39 in the experimental group and 34 in the control group. Data were analyzed using independent t-test, χ²-test, paired t-test, ANCOVA, Mann-Whitney U test, and Wilcoxon signed-rank test in IBM SPSS version 30.0.Results: No significant difference was observed in the dependent variables between the two groups with the exception of learning satisfaction. Learning satisfaction was significantly higher in the experimental group (Z=-3.68, p